Dialectics of Theology and Ecology in Ammatoa ri Kajang in Bulukumba, Indonesia: Paradigm of Tawhidic and Environmental Fiqh in Sulapa Appa - Muliati, Muliati; Hannani, Hannani; Ilham, M.; Anwar, Khairul; Jadi, Soliman Al (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study aims to integrate the Tawhidic paradigm with the local wisdom found in Amatoa ri Kajang to develop a comprehensive framework for ecological fiqh. The research adopts a qualitative approach, utilizing content analysis of the Amatoa ri Kajang text and Islamic theological sources such as the Qur’an and Hadith. By examining the teachings on ecological balance, simple living, and resource management from Amatoa ri Kajang, the study explores how these principles align with Islamic values of tawhid (oneness of God), Khalifa (stewardship), and ihsan (ethical conduct). The results show that both frameworks emphasize the importance of maintaining harmony between humans and nature, with strict prohibitions on environmental exploitation. The originality of this study lies in its integration of Islamic jurisprudence with indigenous wisdom, offering a new perspective on how ecological fiqh can be developed to address contemporary environmental challenges. The research implications suggest that this framework could be institutionalized within Islamic legal systems, providing culturally relevant and ethically grounded solutions for environmental governance.